The most important quality criteria of some home-grown black-currant varieties IV. Gas-chromatographic analysis of aroma - Kuusi, Taina; Siiriä, Alpo; Kuusi, Terttu (Agricultural and Food Science, 1966)
A gas chromatographic study has been made of the volatile aroma components of black-currant. The material consisted of 12 home-grown varieties from 6 localities taken over a period of 2 years, although the series are not complete. Separate investigation was made of the low-boiling and high-boiling parts of the aroma; in the former case, material of two years was studied, and in the latter case, that of one year only. The lower-boiling components were isolated in chilled adsorption tubes from a nitrogen stream led through a berry homogenate at room temperature. Analysis was effected at 80°C with a polyetylene glycol/teflon column (the same mass served as filling for the adsorption tubes). In all, 13 components were registered, although their occurrence, and the amounts in the different samples, were somewhat variable. As regards the different factors, the variety exercised no more than a slight effect on the aroma picture, whereas weather conditions were important, influencing the frequency of the peaks and the general aroma level; a cool summer increased the level. The northernness of the growing locality had a similar effect, although this result its of preliminary nature. The degree of ripeness and the condition had a considerable effect; the level of aromagrams was higher with more ripe samples, and in particular the ethanol content, which forms the bulk of the low-boiling aroma, was increased. A positive correlation was detected between the height of the ethanol peak and the total aroma or aroma number. By contrast, the height of the methanol peak exhibited a slight negative correlation with the degree of esterification of the pectin. The higher-boiling compounds were isolated by vacuum distillation and subsequent extraction with ether. In the gas chromatography, use was made of a butandiol succinate polyester/celite column, and the temperatures were 120 and 150°C. In all, 25 components were observed. Of the various factors, the variety showed a clear-cut influence on the aroma picture, as differences in the occurrence of the peaks and the relative heights were noted between the varieties; in this series, quantitative comparisons between the samples were impossible. The effect of locality and degree of ripeness is less well defined. Organoleptic checking showed that the changes were small in isolation of the lower-boiling components. In contrast, isolation of the higher-boiling compounds induced more changes, so that an aroma fraction obtained in the organic solvent was more terpene-like than the original aroma.